2017
DOI: 10.1097/jnn.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Cognitive Rehabilitation Interventions for Traumatic Brain Injury: A Critical Review of the Literature

Abstract: Background Computer-based interventions have been developed to improve cognitive performance after mild traumatic brain injury, however, a thorough evaluation of this body of research has not been addressed in the literature. Objectives To provide a synthesis and critical review of current research studies that have tested the efficacy of computer-based interventions on cognitive performance after mild traumatic brain injury. Methods A critical review was conducted by identifying relevant studies in the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Previous research has established the effectiveness of restorative cognitive training interventions in patients with acquired brain injury (ABI). 7,10,30 A detailed description of this training program and preliminary efficacy results are reported elsewhere. 26 In short, BrainGames is an iPad application that consists of 8 games designed to train different aspects of cognitive functioning, including sustained, selective, and divided attention, inhibitory control, cognitive flexibility, verbal and visuospatial working memory, updating, and processing speed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has established the effectiveness of restorative cognitive training interventions in patients with acquired brain injury (ABI). 7,10,30 A detailed description of this training program and preliminary efficacy results are reported elsewhere. 26 In short, BrainGames is an iPad application that consists of 8 games designed to train different aspects of cognitive functioning, including sustained, selective, and divided attention, inhibitory control, cognitive flexibility, verbal and visuospatial working memory, updating, and processing speed.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous recent studies and reviews highlighted that rehabilitative cognitive training programs are a promising approach for improving cognitive functioning in brain injury. [7][8][9][10] In addition, the biological mechanisms that underlie cognitive improvements are recently being mapped utilizing magnetic resonance imaging (MRI) techniques. Functional MRI (fMRI) studies have shown functional changes in brain regions after cognitive training (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with previous works in ABI population. Fetta, Starkweather & Jill [13] conducted a systematic review on computer-based cognitive intervention in mild traumatic brain injury population. The authors concluded that there is weak evidence of improvement in working memory after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although the trials included in these studies had methodological problems that could be improved, they showed a general positive small effect on cognition. Previous systematic reviews in mild traumatic brain injury [13], stroke [14] and ABI [15] population suggest that computer-based cognitive interventions might be effective, although the current available evidence is weak and methodologically flawed. To date, no meta-analysis has been performed on computer-based cognitive interventions for ABI.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of several reviews and meta-analyses on VR for stroke ( Lohse et al, 2014 ; Gibbons et al, 2016 ; Laver et al, 2017 ), Parkinson disease ( Dockx et al, 2016 ), multiple sclerosis ( Massetti et al, 2016 ) and multiple neurological conditions ( Cano Porras et al, 2018 ), results about the effectiveness of VR-mediated training are yet inconclusive. One main reason for this is that many studies include small sample sizes as compared to the great variability of the tested clinical populations, which makes extremely difficult to control for other variables such lesion location and size, severity of impairments, phase of recovery and, importantly for cognitive functions, no separation between age or level of education ( Fetta et al, 2017 ). Another key factor is the choice (or lack) of the control group to compare the effect with: for instance, for home rehabilitation, if the effectiveness of a VR-mediated training (with the therapist remotely shaping and monitoring the training program) is compared to that of 1-to-1 therapy sessions of the same intensity and duration with a highly trained clinician, the non-inferiority of the VR-mediated training should be actually considered as a positive outcome, independently of other socio-economic advantages such as reduced costs.…”
Section: Virtual Reality As a Vehicle To Boost Motor-cognitive Neurormentioning
confidence: 99%